MANAJEMEN RRI PRO 2 PEKANBARU DALAM MENGHADAPI EKSISTENSI DI ERA DIGITAL - Vinna "; Hevi Susanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The broadcasting industry is making various efforts in the face of the digital era. Like RRI Pro 2 Pekanbaru which converged media and turned into digital radio. RRI Pro 2 Pekanbaru requires broadcasting management, especially in planning in managing company resources to make changes. Where planning is the first step in broadcasting management which includes goal setting activities and preparing plans and strategies that will be used to achieve the goals of RRI Pro 2 Pekanbaru. This research uses qualitative research methods with research subjects, namely employees and listeners determined by purposive techniques. Data collection is carried out by observation, interviews and documentation. Data analysis techniques use Miles and Huberman models. And the technique of checking the validity of the data using triangulation. The results showed that the planning of RRI Pro 2 Pekanbaru in facing existence in the digital era by setting strategic plans and operational plans so that it can achieve company goals. The strategic plan of RRI Pro 2 Pekanbaru is to mediamorphose into digital radio and converge media by providing multiplatform-based services to make it easier for listeners to access RRI Pro 2 Pekanbaru broadcasts anywhere and anytime. Then the operational plan of RRI Pro 2 Pekanbaru is adjusted to the format that has been set by the RRI Pusat with the segmentation area carried out in short-term planning meetings to see the progress of broadcast programs and long-term planning to measure broadcast programs as well as the implementation of broadcasting activities off air, on air and live streaming. Keywords: Broadcasting Management, Planning, Digital Radio